Strengthening Sales Through Brand Image and Product Quality: An Empirical Study at UD. UMEGA Roti Kacang Hj. Eliya Lubis - Dwi Khairumi; Ratih Amelia; Martin; Lidia Berliana Siboro; Manda Dwipayani Bhastary (Yayasan Bina Bisnis Nusantara Medan, 2025)
This study investigates the influence of brand image and product quality on sales performance at UD. UMEGA Roti Kacang Hj. Eliya Lubis in Tebing Tinggi. A quantitative approach was employed, with data collected through observations, questionnaires, and interviews involving consumers of Roti Kacang Hj. Eliya Lubis. Data analysis was conducted using multiple linear regression with SPSS software. The findings reveal that both brand image and product quality have a positive and significant effect on sales. Among these, product quality plays a more dominant role in driving sales growth, indicating that consistent product excellence is critical to sustaining consumer interest and loyalty. Conversely, while brand image also positively influences sales, its impact is comparatively weaker, suggesting the need for strategic enhancement of brand perception. Strengthening both dimensions is essential for maintaining competitiveness and ensuring sustainable business development in an increasingly dynamic market environment.